2022
DOI: 10.1007/s11366-022-09832-0
|View full text |Cite
|
Sign up to set email alerts
|

Can Debunked Conspiracy Theories Change Radicalized Views? Evidence from Racial Prejudice and Anti-China Sentiment Amid the COVID-19 Pandemic

Abstract: With the advent of the ‘age of conspiracism’, the harmfulness of conspiratorial narratives and mindsets on individuals’ mentalities, on social relations, and on democracy, has been widely researched by political scientists and psychologists. One known negative effect of conspiracy theories is the escalation toward political radicalism. This study goes beyond the exploration of mechanisms underpinning the relationship between conspiracy theory and radicalization to focus on possible approaches to mitigating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…In the political context, belief in conspiracy theories makes it easier for people to be controlled by certain authorities to the point where people are directed to commit acts of violence and undermine democratic institutions [30]. Another study confirmed that at the interpersonal level, belief in conspiracies leads to the justification of violent and radical behavior [31]. Effective refutation of conspiracy theories can have deradicalization effects and reduce prejudice in society [32].…”
Section: Conspiracy Theory and Denialismmentioning
confidence: 90%
“…In the political context, belief in conspiracy theories makes it easier for people to be controlled by certain authorities to the point where people are directed to commit acts of violence and undermine democratic institutions [30]. Another study confirmed that at the interpersonal level, belief in conspiracies leads to the justification of violent and radical behavior [31]. Effective refutation of conspiracy theories can have deradicalization effects and reduce prejudice in society [32].…”
Section: Conspiracy Theory and Denialismmentioning
confidence: 90%
“…Reporting guidelines could be developed to reduce harm caused by media coverage of pandemics in future. For example, a survey study of 300 adults in the USA demonstrated that content-targeted and audience-focused countermeasures to anti-China conspiracy theories related to the pandemic could limit, or even reverse, radicalisation [ 35 ]. Even beyond exacerbating negative perceptions of individuals of Chinese ethnicity, commentaries have highlighted that the overly-simplistic framing of democracy versus authoritarianism in the discourse comparing responses to the pandemic in the UK (and the USA and Western Europe generally) and mainland China, may have inhibited knowledge sharing and cooperation that could have ameliorated the global impact of the pandemic [ 22 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%